Pulse pressure variation and systolic pressure variation in mechanically ventilated children - Johnny Nurman; Antonius H. Pudjiadi; Arwin A. P. Akib (Indonesian Pediatric Society, 2011)
Background In mechanically ventilated patients, changes in breathing patterns may affect the preload, causing stroke volume fluctuation. Pulse pressure variation (PPV) and systolic pressure variation (SPV) are dynamic means of the hemodynamic monitoring in ventilated patients. No study on PPV and SPY in children has been reported to date.Objective To study changes in PPV and SPY values in mechanically ventilated children.Method A descriptive crossô€sectional study was done at the Pediatric Critical Care Unit (PICU), Cipto Mangunkusumo Hospital, Jakarta. Subjects were mechanically ventilated children aged > 12 months. Echocardiography was performed in all patients to determine the cardiac index. Arterial pressure was measured by connecting an arterial line to a vital signs monitor. PPV and SPV were calculated using the standard formulas. Bivariate correlation tests were performed between cardiac index and PPV and between cardiac index and SPV. Receiver operator characteristic (ROC) curve analysis was done to determine the optimum PPV and SPV cut-off points to predict normal cardiac index (2:3.5 L/minute/m2).Results Eighteen patients were enrolled in the study, yielding 48 measurements. Mean cardiac index was 2.9 (SD 1-2.6) L/minute/m2. Median PPV was 18.9 (range 4.1-45.5)% and SPV was 12.1 (range 3.8- 18.9)%. We found strong negative correlations between PPY and cardiac index (r= ; p = ) and SPY and cardiac index (r= ; p = ). To predict nonnal cardiac index, the optimum cut-off point was 11.4% for PPV (100% sensitivity, 100% specificity) and 9.45% for SPV (91.7% sensitivity, 100% specificity).Conclusion In mechanically ventilated children, cardiac index is negatively correlated with PPV and SPV.